Leverage points to improve smoking cessation treatment in a large tertiary care hospital: a systems-based mixed methods study. Issue 7 (2nd July 2019) - Ramsey, Alex T; Prentice, Donna; Ballard, Ellis; Chen, Li-Shiun; Bierut, Laura J
Abstract : Objectives: To generate system insights on patient and provider levers and strategies that must be activated to improve hospital-based smoking cessation treatment. Design: Mixed methods study including a series of in-depth group model building sessions, which informed the design of an online survey completed by healthcare providers and a structured interview protocol administered at the bedside to patients who smoke. Setting: Large, tertiary care hospital in the Midwestern United States. Participants: Group model building : 28 healthcare providers and 22 previously-hospitalised patients; Online survey : 308 healthcare providers; Bedside interviews : 205 hospitalised patients. Primary and secondary outcome measures: Hypothesis-generating, participatory qualitative methods informed the examination of the following quantitative outcomes: patient interest versus provider perception of patient interest in smoking cessation and treatment; patient-reported receipt versus provider-reported offering of inpatient smoking cessation interventions; and priority ratings of importance and feasibility of strategies to improve treatment. Results: System insights included patients frequently leaving the floor to smoke, which created major workflow disruption. Leverage points included interventions to reduce withdrawal symptoms, and action ideas included nurse-driven protocols for timely administration of nicotine replacement therapy. Quantitative data corroborated system insights; for instance, 80% of providers reported that patients frequently leave the floor to smoke, leading to safety risks, missed assessments and inefficient use of staff time. Patients reported significantly lower rates of receiving any smoking cessation interventions, compared with provider reports (mean difference=17.4%–33.7%, p<0.001). Although 92% of providers cited patient interest as a key barrier, only 4% of patients indicated no interest in quitting or reducing smoking. Conclusions: Engaging hospital providers and patients in participatory approaches to develop an implementation strategy revealed discrepant perceptions of patient interest and frequency of hospital-based treatment for smoking. These findings spurred adoption of standardised point-of-care treatment for cigarette smoking, which remains highly prevalent yet undertreated among hospitalised patients.